Monitoring Concept for CO2 Storage at the Ketzin Pilot Site, Germany – Post-injection Continuation Towards Transfer of Liability. (November 2016) - Wipki, Mario; Ivanova, Alexandra; Liebscher, Axel; Lüth, Stefan; Möller, Fabian; Szizybalski, Alexandra; Wiese, Bernd; Zimmer, Martin
Abstract: At the Ketzin pilot site the GFZ German Research Centre for Geosciences has developed an interdisciplinary monitoring concept for CO2 storage, which incorporates different permanent and periodic measurements. The concept mainly bases on seismic, geoelectric, borehole and geochemical monitoring and focusses on the storage complex, the overburden, the surface and the wellbores. After the end of injection in August 2013, this concept is now continued and applied for post-injection monitoring to address long-term site performance to finally transfer liability to the competent authority. Experiences gained at the Ketzin site may be transferred to other CO2 storages pilots and also industrial-sized projects.